2018
DOI: 10.1111/hsc.12676
|View full text |Cite
|
Sign up to set email alerts
|

Relational aspects of mastery for frail, older adults: The role of informal caregivers in the care process

Abstract: Frail, older care recipients are often thought of as individuals with a decreased mastery of everyday life skills. Various authors have proposed to acknowledge a relational dimension of mastery, defined as the ability to maintain control over one's life with the help of others. This study explores how frail, older adults experience relational aspects of mastery and the role of their informal caregivers in maintaining these aspects of mastery over the care process. Qualitative interviews (N = 121) were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
3
8
1
Order By: Relevance
“…We saw a high degree of reluctance to ask, especially in relationships where reciprocity is the norm. This finding also shows that we cannot see care recipients as only passive and dependent, as was also noted by Lambotte et al ().…”
Section: Discussionsupporting
confidence: 84%
“…We saw a high degree of reluctance to ask, especially in relationships where reciprocity is the norm. This finding also shows that we cannot see care recipients as only passive and dependent, as was also noted by Lambotte et al ().…”
Section: Discussionsupporting
confidence: 84%
“…As in Lambotte et al (2019), our results showed how family carers can enact their agency for the behalf of the person with memory disorder. In our findings, they provided a larger share of the accounts concerning influencing care.…”
Section: Discussionsupporting
confidence: 61%
“…The common understanding of agency has been criticized for being language-centered (Boyle, 2014) and too heavily based on cognitive and intellectual abilities (Kontos, 2004). Even though our study showed that cognitive decline makes a person’s own involvement more difficult (also in Bosco et al, 2019; Lambotte et al, 2019), our study demonstrated that the abilities of people with memory disorders are very diverse and strongly connected to each individual’s personal situation. Our data show that people with memory disorders can express their preferences, even if the way they express themselves might be less determined or fluent than of people with intact cognition.…”
Section: Strengths and Limitationscontrasting
confidence: 61%
See 2 more Smart Citations